The Failure of European Governance of the Crisis. (30th June 2014) - Bilbao-Ubillos, Javier
Abstract : The current euro crisis, considered by the IMF to be the new heart of the international economic crisis, has its historical roots in the process of construction of the European Monetary Union (EMU). The resulting architecture of economic governance in the EU has revealed itself to contain serious shortcomings in both ideological terms (design of a coherent exit strategy) and institutional terms (procedures, irreversibility and implementation times of the decisions made). As a result, the responses made by Europe have been late, hesitant, sometimes lacking in intensity and inconsistent in their attempts to manage the crisis.